Implementasi Kurikulum ISMUBA (Islam Muhammadiyah Bahasa Arab) Dalam Imtak dan Iptek di SMA Muhammadiyah Pangkalpinang - Zidane Romadhonie (Universitas Muhammadiyah Bangka Belitung, 2024)
This research discusses the implementation of the ismuba curriculum (Islam Muhammadiyah Arabic Language) at SMA Muhammadiyah Pangkalpinang. Referring to the problems faced by the world of education in the era of globalization and significant technological developments. Curriculum strategy is absolutely necessary to respond to the development of globalization, democratic life, respond pro-actively to the development of information, science. Curriculum implementation is important in education to create a productive, efficient and creative learning process. The purpose of this study was to determine the teacher's understanding of the ISMUBA curriculum in the teaching and learning process. Islam basically does not view religious knowledge (imtaq) and general science (science and technology) separately, because both come from one source, namely Allah SWT. Knowledge in religion is knowledge that comes directly from Allah swt. Al-Islam Kemuhammadiyahan Arabic Education (ISMUBA) is a special characteristic and advantage for Muhammadiyah schools and madrasahs. Progressive Muhammadiyah education is organized with an integrative-holistic modern Islamic education system. Keywords: development, curriculum implementation, and knowledge